Penerapan Sistem Crm (Customer Relationship Manajemen) Untuk Meningkatkan Hubungan Pelanggan Studi Kasus Pada Pt. Tujuhlangit Lintas Nusantara - Khambali, Ahmad; Nur Aini, Fadhila (Neraca, 2024)
PT. Tujuhlangit Lintas Nusantara is a company engaged in services, especially internet service providers with fiber optic technology that offers corporate, residential and partnership internet package services. As technology advances, competition between internet service companies is getting stronger and increasingly dependent on the quality and service of each company. The existing system at PT Tujuhlangit Lintas Nusantara still has shortcomings and does not cover all the needs of the company. From this problem, a good business strategy is needed, namely using the development of a CRM (Customer Relationship Management) system that is automated in the form of a system. The methods used in this research are literature studies in the form of journals, observations and interviews. While the method used for CRM development is to use the waterfall method which is a general methodology in system development. Tools for design using UML (Unified Modeling Language). The results of the analysis concluded that CRM is the main business strategy choice at PT Tujuhlangit Lintas Nusantara. And from these problems, a CRM system will be created for the purpose of attracting new customers, customer satisfaction, obtaining higher sales, and maintaining customer loyalty in order to contribute to achieving business strategies at the company. REFERENSI Chadhiq, U. (2015). Customer Relationship Management ( CRM ) : Pilihan Strategi untuk Meraih Keunggulan Bersaing. Dharma Ekonomi, 18(33), 1–14. Rahmanto, W., Juanita, S., Suryadi, L., & Sutrisno, J. (2023). Implementasi E-Crm Untuk Layanan Keluhan Implementation of E-Crm for Customer Complaints Service At Pt . Information Tools Achievement. 2(April), 934–942. Regiani, E., Dwiputri, F. A., Amaliyah, S., & Herlambang, Y. T. (2023). DAMPAK PENGGUNAAN TEKNOLOGI INTERNET TERHADAP DALAM KELUARGA cepat , tepat dan efisien . Informasi-informasi baru yang disajikan tersebut dapat memperkaya. 4(3), 2888–2899. Damanik, E., & Siregar, I. M. (2021). Pengembangan Sistem Customer Relationship Management Berbasis Web Pada Pt. Terus Mega Tara Jakarta. Jurnal Teknik Informasi Dan Komputer (Tekinkom), 4(1), 60–69. Eka Fitriany, A., & Mulyono, H. (2023). Sistem Informasi Customer Relationship Manajemen (CRM) Berbasis Web Pada PT. Patria Cabang Mendalo. Jurnal Manajemen Sistem Informasi, 8(1), 67–77. Samudra, Y. (2023). Penerapan Metode Design Thinking Dalam Pengembangan Sistem CRM , Cash Flow , dan Management Stock Inventory Pada Aplikasi Krealogi. 1(5), 1283–1296. Galih, Alivia, N., & Sandi Apriandi. (2023). Perancangan Sistem Customer Relationship Management (CRM) Berbasis Website di PT Aguna Amreta Ardaya. TEMATIK, 10(1), 113-123. Nugraha, R. (2022). Rancang Bangun Sistem Crm (Customer Relationship Management) Berbasis Web Dengan Pola Mvc. JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 9(1), 70-85.